The Role of Internet Addiction and Basic Psychological Needs in Explaining the Academic Procrastination Behavior of Adolescents - Can, Sermin; Zeren, Serife Gonca (CUKUROVA UNIV, 2019)
This study focuses on examining how the academic procrastination behavior of adolescents is explained through Internet addiction and basic psychological needs. The study was conducted on 493 female and 421 male participants, a total of 914 students, studying in different types of high schools in Istanbul, Turkey. The Pearson Product-Moment Correlation Coefficient and Path Analysis were used in the data analysis. According to the findings, the academic procrastination behavior of adolescents has medium level, positive and significant relationships with their Internet addiction levels. It also has weak level, negative and significant relationships with competence, relatedness and autonomy needs, which are sub-dimensions of basic psychological needs. It was observed that Internet addiction levels and the need for competence directly and significantly, and needs for autonomy and relatedness indirectly explain the academic procrastination behavior of adolescents. In addition, it was found that Internet addiction directly, negatively and significantly affects basic psychological needs, and indirectly accounts for the academic procrastination behavior of adolescents through basic psychological needs.
Keywords: Procrastination; Academic procrastination; Internet addiction; Basic psychological needs; SELF-DETERMINATION THEORY; COLLEGE-STUDENTS; SATISFACTION; MOTIVATION; EFFICACY; AUTONOMY; TRAIT; LIFE; RELATEDNESS; ANTECEDENTS; Education & Educational Research